The antifungal activity of ray fungum against the fusarium wilt causal agent of tomato - Sidorova, Svetlana G. (Experimental Biology and Biotechnology, 2019)
The antifungal activity of genus Streptomyces strains (from collection of department of microbiology, Belarusian State University) against the fusarium wilt causal agent of tomato micromycetes Fusarium oxysporum f. lycopersici (Sacc.) Snyder and Hansen were studied in laboratory model experiments. Dynamic of micromycete colonies growth, morphology, color and fruiting intensity were analyzed. The screening of tested strains of genus Streptomyces for their anti-wilt activity has showed that the strain 10 influences the inhibiting (more than 60 %) effect on all fusaruim isolates: high-pathogenic (Fol 1), middle-pathogenic (Т 2) and low-pathogenic (Т 11). Their colonies growth were blocked from the 4th day of joint cultivation. The strain 11 has been an antagonist for the isolates Fol 1 and T 2, and the strain 20 – for the isolate T 11. Strains 18 and 35 demonstrate no antifungal activity to all F.oxysporum f. lycopercisi isolates under study.
Keywords: fusarium; tomato; ray fungum; phytopathology